Comprehension Instruction for High School Learning Disabled Students - Craig Darch (Journal of Research in Rural Education, 1988)
The purpose of this paper is to present an overview of an alternative instructional approach for helping high school students with learning disabilities comprehend content area instruction. The instructional approach combines the use of Direct Instruction and advanced organizers. This paper begins with a general review of relevant research in each of these areas. This review is followed by a discussion of two recently published studies [5, 6] which provide support for combining Direct Instruction teaching procedures and the use of advanced organizers as a method to enhance the comprehension skills of high school learning disabled students placed in regular classrooms. In the final section of this paper, general methods teachers can use to successfully teach learning disabled students placed in regular classrooms are identified and discussed.